2015
DOI: 10.1089/lap.2015.0188
|View full text |Cite
|
Sign up to set email alerts
|

Early and Midterm Outcome After Laparoscopic Fundoplication and a Minimally Invasive Endoscopic Procedure in Patients with Gastroesophageal Reflux Disease: A Prospective Observational Study

Abstract: LTF and the Stretta procedure were equally effective in controlling GERD symptoms and reducing PPI use. However, LTF can achieve more improvement on typical symptoms and has a lower rate of re-operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Gastroesophageal reflux (GER), and especially nocturnal GER (nGER), is associated with many symptoms from the respiratory tract, often asthma symptoms [ 1 3 ]. However, it is not fully known how GER patients with asthma symptoms differ from other asthma patients, and what the pathogenic mechanisms are.…”
Section: Introductionmentioning
confidence: 99%
“…Gastroesophageal reflux (GER), and especially nocturnal GER (nGER), is associated with many symptoms from the respiratory tract, often asthma symptoms [ 1 3 ]. However, it is not fully known how GER patients with asthma symptoms differ from other asthma patients, and what the pathogenic mechanisms are.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 3 ] Since the first laparoscopic Nissen fundoplication (LNF) was described in 1991, [ 4 ] extensive studies regarding laparoscopic antireflux surgery have been reported, demonstrating an established role of fundoplication for the treatment of GERD. [ 5 7 ] As the most widely used surgical treatment of GERD, LNF is associated with some unwanted functional disorders, such as dysphagia, gas-bloating syndrome. To minimize the risk of these complications, a variety of modifications of LNF have been launched.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, up to 40% of GERD patients are refractory to PPIs[ 14 , 15 ]. In our previous study, we demonstrated that laparoscopic Toupet fundoplication (LTF) was more effective than the Stretta procedure in controlling GERD symptoms[ 16 ]. However, the effects of reflux on the upper respiratory tract, including chronic cough, asthma, expectoration, breathlessness and laryngospasm, seriously affect the quality of life of GERD patients [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%